2023
DOI: 10.1093/cid/ciac967
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus Disease Among Children <5 Years in 3 Sub-Saharan African Countries: Findings From the Vaccine Impact on Diarrhea in Africa (VIDA) Study, 2015–2018

Abstract: Background To address a paucity of data from sub-Saharan Africa, we examined the prevalence, severity, and seasonality of norovirus genogroup II (NVII) among children <5 years old in The Gambia, Kenya, and Mali following rotavirus vaccine introduction. Methods Population-based surveillance was conducted to capture medically-attended moderate-to-severe diarrhea (MSD) cases, defined as a child 0–59 months old passing ≥3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(55 reference statements)
2
2
0
Order By: Relevance
“…No resistance was observed for ceftriaxone [ 3 ]. While previous studies have shown diarrhea seasonality aligning with the rainfall pattern, climate change is likely an important driver influencing diarrhea epidemiology and even etiology-specific prevalence in Kenya, consistent with observations from other similar settings in Africa as described elsewhere [ 26–28 ].…”
Section: Historical Shigella Incidence Prevalence ...supporting
confidence: 88%
“…No resistance was observed for ceftriaxone [ 3 ]. While previous studies have shown diarrhea seasonality aligning with the rainfall pattern, climate change is likely an important driver influencing diarrhea epidemiology and even etiology-specific prevalence in Kenya, consistent with observations from other similar settings in Africa as described elsewhere [ 26–28 ].…”
Section: Historical Shigella Incidence Prevalence ...supporting
confidence: 88%
“…A previous norovirus survey in this study area did not find a statistical difference between symptomatic and asymptomatic subgroups [ 27 ]. The findings suggest that norovirus is strongly associated with VAGE in this region, as reported in other low- and middle-income countries [ 40 , 41 ]. HNoV infections level were higher (59%) in hospitalised patients compared to outpatients (41%), suggesting that norovirus is actively involved in AGE symptoms and diarrhoea disease ( p = 0.0129).…”
Section: Discussionsupporting
confidence: 78%
“…In this study, HNoV predominated among children between 6 and 23 months old. Recently published data showed that norovirus disease burden is mostly experienced at this age range in African countries [ 40 ]. A similar finding was observed in the MALED group study, wherein norovirus infection peaked after 6 months [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The objectives of the research presented here were to describe the prevalence of episodes attributable to adenovirus 40/41, astrovirus, sapovirus, and rotavirus and the clinical characteristics of these cases; to examine the severity of attributable cases of adenovirus 40/41, astrovirus, and sapovirus compared with rotavirus; and to describe the seasonality of these viruses. The compelling need to better define the global burden of norovirus in low-income settings [ 27 ] is the subject of a separate analysis [ 28 ].…”
mentioning
confidence: 99%